Extraction Optimization and Characterization of Cellulose Nanocrystals from Apricot Pomace - Kasapoglu, Ekin Dincel; Kahraman, Sibel; Tornuk, Fatih (MDPI, 2023)
Apricot pomace (AP) is lignocellulosic agro-industrial waste that could be considered a good source for cellulose-based, value-added compounds. In this study, conditions for cellulose nanocrystals' (CNCs) extraction from apricot pomace (AP) were optimized using Response Surface Methodology (RSM) based on the extraction yield, and the resulting CNC was characterized using Fourier transform infrared (FTIR) spectroscopy, Scanning Electron Microscopy (SEM), Transmittance Electron Microscopy (TEM), Thermogravimetric Analysis (TGA), and X-Ray Diffraction (XRD). The maximum CNC yield (34.56%) was obtained at a sulfuric acid concentration of 9.5 M within 60 min. FTIR analysis showed that noncellulosic components were gradually removed from the pomace. A morphological analysis of the nanocrystal was performed using SEM and TEM. CNCs were in the range of 5-100 mu m in diameter and appeared as individual fibers. TGA analysis of the CNC sample revealed good thermal stability around 320 degrees C. The crystalline index (%CI) of the CNC obtained from AP was determined to be 67.2%. In conclusion, this study demonstrated that AP could be considered a sustainable source for value-added compounds such as CNCs to contribute to a circular economy.
Keywords: apricot pomace; cellulose nanocrystals; agro waste; optimization; SULFURIC-ACID HYDROLYSIS; PINEAPPLE LEAF; NANOCELLULOSE; FIBERS; BIOCOMPOSITES; NANOFIBERS; MORPHOLOGY; WASTE; PEELS; Food Science & Technology